MANFAAT PANGAN FUNGSIONAL DAN PANGAN HERBAL DALAM MENINGKATKAN IMUNITAS TUBUH DI MASA PANDEMIC COVID-19 - Mulyati, Sri (Jurnal Pengabdian Dinamika, 2021)
The Covid-19 pandemic is not over yet, so people are required to always comply with health protocols (5M), maintain body immunityand do the vaccine,all of this to prevent exposure covid-19. To increase immunity needsfunctional foods and herbal foods. The purpose of this dedicationis to socialization about benefits of functional foods and herbal foods in the Sukasari village, Kadu hejo, Pandeglang community. The dedicationmethod used web seminar, but the results are less effective, because the village community is still foreign to attend counseling through online seminars, they are passive and only village officials who asked. The weakness web seminar cannot be measured how this knowledge, attitude and skills after attending the seminarand not many people who follow this socialization. The conclusion is the web seminarcannot be held for the village community, because it is less effective.